Pemanfaatan Limbah Serbuk Kayu dengan Zat Aditif Anti Stripping Agent Terhadap Uji Durabilitas AC-WC (Asphalt Concrete–Wearing Course) - Ivo Neyra Rahman; Devina Sinta Damara; Riza Susanti; Asri Nurdiana (Universitas Diponegoro, 2024)
The increasing number of vehicles each year in Indonesia causes excessive repetition of loads that occur on road pavements, as well as extreme weather changes resulting in damage to the pavement layer, especially at the level of durability, especially in the AC-WC layer. The use of sawdust waste in the AC-WC mixture has met the marshall test values/characteristics, but it is necessary to test its durability; a high durability value indicates that the road is more durable and resistant to weather and water. Therefore, it is necessary to improve the quality of road pavement by adding anti-stripping agent additives at levels of 0.3%, 0.4%, and 0.5% to the AC-WC mixture of 25% wood powder waste substitution in order to improve the properties of asphalt in increasing the coating of asphalt with aggregates in a wet state to produce stronger bonds to extend the life of the road. This study aims to determine the effect of adding anti-stripping agent additives in AC-WC mixtures with sawdust waste on durability tests. Experimental tests were conducted using the research method at the Civil Engineering Laboratory of Diponegoro University Vocational School Semarang. The study results obtained a durability value based on the calculation parameters of the Residual Strength Index (IKS) based on the General Specifications of Bina Marga 2018 (Rev 2), which shows the durability of AC-WC asphalt. The results of marshall testing obtained based on averages include VIM 4.11%, VMA 13.15%, VFA 77.33%, Stability 1893.73 Kg, Flow 2.17 mm and MQ 1070.03 kg/mm from 25% wood powder waste variation with anti-stripping agent additives 0.3%; 0.4%; 0.5% in AC-WC wear layer has met the General Specifications of Bina Marga 2018 (Rev 2). The average durability values of IKS with sequential soaking time are 24 hours 92.24%, 48 hours 88.87%, and 72 hours 80.08%.